Factors Associated with Adherence to Physiotherapy Among Children Living with Physical Disabilities - Adu, A.A. (University of Ghana, 2018)
INTRODUCTION: Physiotherapy has proven to be very beneficial in improving function and quality of life among children with physical disabilities. Nonetheless, adherence to treatment is an important factor which can influence the outcome of treatment. Children with disability are regrettably at increased risk of non-adherence because they have to rely on care-givers to access physiotherapy and perform their home exercises. This study sought to determine factors associated with adherence to physiotherapy among children living with physical disabilities within four health facilities in the Greater Accra Region. METHODOLOGY: This study was a facility based cross-sectional study involving eighty five caregivers of children with physical disabilities. Following informed consent, questionnaires and structured interview guides were used to obtain information on socio-demographics, knowledge on physiotherapy and factors associated with adherence to keeping therapy appointments and home exercise program. Data was analysed using STATA version 14 and Nvivo 11. Associations and strengths of association were determined using chi-square and logistic regressions respectively. Significance level was set at p< 0.05 and 95% confidence interval (CI). RESULTS: A little over 95 per cent of the caregivers had adequate knowledge on physiotherapy. Adherence to keeping therapy appointment was 81.2 per cent while adherence to home exercise program was 58.8 per cent. Caregivers‟ seeking of other forms of treatment (OR=0.24, CI 95%, 0.07- 0.79), perception of difficulty of their children‟s exercise regimen (OR=9.59, CI 95%, 1.64-56.09), number of children (OR=3.40, CI 95%, 0.76-15.11)(OR= 1.25, CI 95%, 0.43-3.66), perception of disease severity (OR=1) and clashing of home exercises with other responsibilities (OR=9.23, CI95%, 3.19-26.69) were associated with adherence to keeping physiotherapy appointments and home exercises. CONCLUSION: Generally, caregivers adhered very well to therapy with their health seeking behaviour, clashing of home exercise regimen with other pertinent responsibilities, number of children, perceived difficulty of therapy and perceived severity of child‟s medical condition being predictors of good adherence.
Keywords: Physical Disabilities; Physiotherapy; Children; Adherence